A relação campo-cidade sob a ótica da transformação de um bairro rural em distrito municipal : o caso de Moçambo, no município de Muzambinho-MG, Brasil - Letícia Almeida Araújo; Ana Rute do Vale (Confins)
The relations between the countryside and the city have always been marked by complexities and particularities that can be evidenced when studying a municipal district, once considered the interface of this relationship, based on academic theories. This is the case of the district of Moçambo, located in the municipality of Muzambinho-MG, an old rural district that had a past with a certain development, when it housed in its headquarters the Moçambo Station of the Mogyana Railway Company, used for the flow of agricultural products, especially coffee, and was responsible for the population concentration around it. There was, therefore, a great flow of people, passengers and goods, which practically disappeared with the deactivation of the railroad at the end of the 1960s, and had its resumption with the development of coffee farming in the municipality and in the region from the 1970s. Despite the rural way of life of this population, the neighborhood was transformed into a municipal district in 2015, with all the consequences of this process, especially the immediate collection of urban taxes and the reclassification of the population of the district headquarters as urban, as determined by IBGE. Thus, the present work seeks to understand how the rural-city relationship was established in this transformation from a rural district to a district, in the context of a municipality, whose headquarters are small and which, because of the predominance of agricultural activities, has quite pronounced manifestations of rurality. The results were obtained through interviews and the application of a semi-structured questionnaire and showed that political interests in this process were much greater than those of the local population that besides having been consulted about the transformation of Moçambo into a district, it has still not perceived improvements in terms of urban infrastructure, such as water and sewage treatment and paving of streets.